Improved event-triggered control for a chemical tubular reactor with singular perturbations. (April 2022) - Song, Xiaona; Zhang, Qiyuan; Song, Shuai; Ahn, Choon Ki
Abstract: This study proposes an improved event-triggered controller based on spatiotemporally sampled data for the temperature and concentration profiles of a chemical tubular reactor subject to singular perturbations. The resulting system contains not only the spatial location characteristics but also multiple-time-scale features, which results in problems in the system design. To reduce the network communication burden, a spatiotemporal data approach is employed, based on which an improved spatiotemporal-event-triggered mechanism is proposed. Furthermore, a point-control strategy is developed to reduce the system-control costs for limited actuators. Finally, some conditions that guarantee stability of the chemical tubular reactor system are given, and the simulation results are presented to demonstrate the validity and applicability of the proposed design. Highlights: The stability analysis of a reactor with singular perturbations is given. An improved spatiotemporal event-triggered mechanism is first proposed. This work designs a point-control method to balance the cost and control effect.